Exploring The Meaning of Existence in The Thought of Jean Paul Sartre with Abd Al-Rahman Badawi - Dewi Sofiyatul Karima (Mimbar Agama dan Budaya, 2023)
Existentialism is a philosophical doctrine that has the basis of human existence, then enters the field of literature as one of the best intellectuals and arts to reach humans. Jean Paul Sartre (1905-1980) as the triumphant bearer who declared himself an atheist existentialist. The existence of man precedes his essence as man determines his own nature freely. Based on man's freedom in creating his own essence, Sartre formulated "man is nothing else but that which he makes of himself" which in existentialism itself has the concept of commitment (الإلتزام). Existentialists explain that any action done by humans is the basis of human commitment itself. The relationship between existentialism and literature is proven that some existentialist figures play a role in writing literature, even some of them understand about literature. So is the work of Abd al-Rahman Badawi as an Arab writer with existentialism.